Impact of informal caregiving on caregivers' subjective well-being in China: a longitudinal study - Mingmei Cheng; Hualei Yang; Qian Yu (BMC, 2023)
Abstract Background While informal caregiving is crucial for improving and maintaining health of the elderly, there is limited evidence of its potential effect on caregivers' wellbeing. Understanding this effect is important for policy makers to design effective long-term care policies. This longitudinal study aims to investigate the impact of informal caregiving on caregivers' subjective wellbeing in China. Methods Three waves (2016, 2018, 2020) of data from the China Family Panel Studies (CFPS) are constructed for empirical analysis. Ordered logit model is first used to estimate the effect. Fixed effects ordered logit model and mixed effects ordered logit model are further employed to control for the possible bias from unobserved individual heterogeneity. Results Informal caregiving significantly reduces caregivers' subjective wellbeing and the negative effect is stronger for high-frequency caregivers. Subgroup analysis reveals that informal caregiving imposed greater negative impacts on women, those living in rural areas, being married, working, and living separately from parents. Further analysis of mechanism indicates that decrease in wage income, leisure and sleep time were channels through which informal caregiving affects caregivers' well-being. Conclusion When policy makers formulate sustainable long-term care policies and home support services, interventions to improve caregivers' stress-coping skills and ensure their engagement in leisure and social activities could be adopted to mitigate the negative effects on caregivers' subjective well-being.